Additional of EM4 and molasses in feeds on the growth and survival rate of snakehead (Channa striata) - Cut Dara Dewi; Usman Maulana; Sayyid Afdhal El Rahimi; Ismarica Ismarica (Depik, 2023)
This study aims to determine the effect of giving EM4 probiotics on the growth and survival rate of snakehead (Channa striata). This research was carried out at the Fish Hatchery Laboratory, Faculty of Marine and Fisheries, Universitas Syiah Kuala. This study was conducted using a Complete Randomized Design (CRD) method with 4 treatments used, namely A (control), B (EM4 6 ml/kg of feed), C (EM4 8 ml/kg of feed), and D (EM4 10 ml/kg of feed). The results showed that the addition of 10 ml/kg of feed of EM4 probiotic resulted in an absolute length growth of 1.60±0.17 cm, an absolute weight growth of 1.85±0.18 gram, a specific growth rate of 1.97±0.10 % per day, a feed conversion ratio of 1.56±0.03, feed efficiency 64.19±1.41 % and survival rate 97.78±3.85 %. The results of this study can be concluded that the addition of probiotic EM4 10 ml/kg of feed can increase the growth and survival rate of snakehead (Channa striata).Keywords:Channa striataEM4Commercial feedGrowthSurvival rate